2020
DOI: 10.1186/s12864-020-6452-0
|View full text |Cite
|
Sign up to set email alerts
|

Changes in life history traits and transcriptional regulation of Coccinellini ladybirds in using alternative prey

Abstract: Background: Ladybird beetles (Coleoptera, Coccinellidae) are highly diverse in their feeding habits. Most of them are specialist feeders, while some can have a broad spectrum of prey. As a representative group of generalists, the tribe Coccinellini includes many aphidophagous species, but members of this tribe also feed on other hemipterous insects including coccids, psyllids and whiteflies. As a result, several species are effective biological control agents or invasive species with serious non-target effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
(52 reference statements)
0
2
0
2
Order By: Relevance
“…Among these species, four are ladybird species of the Coccinellidae family ( Coccinella septempunctata , Propylea japonica , Harmonia axyridis and Cryptolaemus montrouzieri ) with available genome sequences, and they exhibit apparently a relatively wider prey range than N. pumilus . These four ladybirds can feed on aphids, mealybugs and whiteflies [ 1 ], while N. pumilus mainly feeds on the pests of the Icerya [ 103 ]. There have been several genomes of H. axyridis sequenced, among which we only selected a chromosome-level genome from Chen et al (2021) [ 33 ] to use in the analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these species, four are ladybird species of the Coccinellidae family ( Coccinella septempunctata , Propylea japonica , Harmonia axyridis and Cryptolaemus montrouzieri ) with available genome sequences, and they exhibit apparently a relatively wider prey range than N. pumilus . These four ladybirds can feed on aphids, mealybugs and whiteflies [ 1 ], while N. pumilus mainly feeds on the pests of the Icerya [ 103 ]. There have been several genomes of H. axyridis sequenced, among which we only selected a chromosome-level genome from Chen et al (2021) [ 33 ] to use in the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Ladybirds (Coleoptera, Coccinellidae) are a group with diverse feeding habits. Most of them are specialist feeders, while some species have a much wider range of prey [ 1 ]. Evolutionary studies have suggested that the ancestors of modern ladybirds switched from mycophagy to scale insects feeding, and some species have even shifted the feeding behaviors to plants, mites, whiteflies and aphids [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Este coccinélido es una de las especies dominantes en ensamblajes de depredadores asociados a plantas no cultivadas que crecen naturalmente en el agroecosistema. De acuerdo con Chen et al (2020), es una especie generalista que se alimenta de áfidos, ácaros, escamas y moscas blancas, pero también puede nutrirse de alimentos que no son presas.…”
Section: Porcentajes De Abundancia (%) /unclassified
“…y a plantas no cultivadas que crecen naturalmente en este agroecosistema en el suroccidente colombiano (Melo-Cerón & Manzano, 2017). Hippodamia convergens es una especie generalista que se alimenta de áfidos, ácaros, escamas y moscas blancas (Chen et al, 2020) pero también puede nutrirse de alimentos que no son presas (Lundgren, 2009). Debido a que el depredador se hospeda en plantas no cultivadas, en presencia o ausencia de los áfidos, y que U. nigrotibium es un áfido grande (0.5-0.8 mm en promedio), vistoso y expuesto a la depredación, mientras que R. maidis es un áfido pequeño (0.1-0.3 mm) que se encuentra oculto dentro de la panícula de maíz, o expuesto en la inflorescencia, nuestra primera hipótesis es que H. convergens presenta una tasa de depredación en estado de larva más alta sobre U. nigrotibium y esto favorecería el desarrollo del coccinélido.…”
Section: Introductionunclassified